Proposta de capacitação para enfermeiros da atenção básica à saúde subsidiada na avaliação multidimensional da pessoa idosa - Wanderley, Barbara Maria Soares Pereira (2019)
Population aging is a global phenomenon. In Brazil, a person with a chronological age of 60 years old or more is considered elderly, then being supported by the Law No. 8,842/94, since it is the first specific law aimed to guarantee the rights of elderly people in Brazil. Furthermore, the Law No. 8,842/94 addresses the Elderly National Policy covering the National Policy on Elderly Health, which targets to recover, maintain and promote the autonomy and independence of elderly persons, directing collective and individual health measures for this purpose, in accordance with the principles and guidelines of the Sistema Único de Saúde (SUS) [Brazilian Unified Health System]. Bearing the aforesaid in mind, it is believed that the Family Health Strategy constitutes a great framework for comprehensive elderly health care, as it is the main gateway to the health system, as well as its proximity to the community and home care, which enables a multidisciplinary professional approach based on the familyhood reality experienced by the elderly person. In this scenario, the registered nurse plays a fundamental role, as a member of the minimum required team, developing both managerial and planning actions, as well as directing care and educational practices. It is a methodological study that aims to identify in the literature evidences regarding the nursing care systematization towards elderly people in primary health care; to verify the experience of registered nurses concerning the multidimensional assessment of elderly people in primary health care; moreover, to propose training pedagogical approach for nurses based on the principles of multidimensional assessment of elderly people in primary health care as a method to implement the nursing consultation. The study is going to be performed with 26 registered nurses from the Family Health Units of the Health District V in João Pessoa city, Paraíba State, who will answer to an interview script. Likewise, it is contemplated that this research is going to bring fundamental contributions to the nursing profession, since it encourages the critical-reflexive thinking of the care daily practices provided to elderly people and their families in the FHS, while promoting a pondering attitude by the professionals involved vis-à-vis always be looking for knowledge, skills, and performance improvements through permanent education, aiming at competent, humanized and resolutive primary care.